Indirect methods for estimating the hydraulic properties of unsaturated soils (U.S. Department of Agriculture, 1989)
By comparing the measured and estimated conductivities for the group of data, the accuracy of the approach could be determined for various conditions. The analysis consisted of comparing measured and estimated conductivities using the predictive method (i.e., when the unsaturated hydraulic conductivity is assumed to be unknown), the simultaneous method (i.e., when both water retention and unsaturated hydraulic conductivity data are available), a matching point (at a point somewhat dryer than saturation) to scale the estimated value of the conductivity, and a methods involving the adjustment of Mualem’s empirical factor, 4 to improve the fit between the measured and estimated conductivity. The results indicate that for this group of data, the best estimates of the unsaturated hydraulic conductivity are obtained using either the predictive approach with a matching point, or the simultaneous approach using a 6-parameter fit (i.e., including 0,. O,, a. n, (and K, in the fitting procedure). Surprisingly, the worst and most biased estimates were obtained using the simultaneous approach with a S-parameter fit (i.e., when K, was fixed).